Symposium on Pavement Fatigue Prediction held in Laramie, Wyoming, USA - Bastian, Ernest (2025)
The Western Research Institute, in cooperation with the Federal Highway Administration (FHWA), hosted the "Symposium on Pavement Fatigue Prediction" in Laramie, WY. The event lasted for two days (July 18–20). The symposium was organized to bring together the world’s leading researchers in the field of fatigue damage in asphalt pavements.